An optimal k of kth MA-ARIMA models under a class of ARIMA model. Issue 12 (18th June 2017) - Dawoud, Issam; Kaçiranlar, Selahattin
ABSTRACT: In this article, we discuss finding the optimal k of (i) k th simple moving average, (ii) k th weighted moving average, and (iii) k th exponential weighted moving average based on simulated ARIMA ( p, d, q ) model. We run a simulation using the three above examining methods under specific conditions. The main finding is that 5th exponential weighted moving average (5th EWMA) ARIMA model is the best forecasting model among others, which means the optimal k = 5. For Turkish Telecommunications (TTKOM) stock market, real data reveal the similar results of simulation study.